Pengaruh Electronic Word of Mouth Instagram dan Kualitas Pelayanan Terhadap Minat Kunjungan Balik Pasien ke RSI Hasanah Muhammadiyah Mojokerto dengan Brand Image Sebagai Variabel Mediasi - Feni Wahyuningsih; Wani Devita Gunardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The world has developed rapidly in all aspects, one of which is in the field of technology. This affects the increase in electronic word-of-mouth (eWOM) which has a major impact on the interest in returning to a service. eWOM plays an important role in shaping patient perceptions of the quality of hospital services. Brand image also plays an important role, especially amidst the increasingly tight competition between government and private hospitals. This study aims to determine the influence of electronic word of mouth (eWOM) Instagram and service quality on patient return visit interest to RSI Hasanah Muhammadiyah Mojokerto with brand image as a mediating variable. The research sample was taken from 100 respondents of RSI Hasanah Muhammadiyah Mojokerto patients with an age range of 18-75 years. Data were obtained through questionnaires distributed randomly both online via google form, and offline using questionnaire sheets. The analysis technique used was SEM-PLS (Structural Equation Model-Partial Least Square) using SmartPLS software version 3.3.2. From the results of the analysis, it was obtained that eWOM did not have a significant effect on the intention to return where the p value was 0.096> 0.05, while service quality had a significant effect on the intention to return with a p value of 0.002 <0.05. eWOM did not have a significant effect on brand image where the p value was 0.582> 0.05, while service quality had a significant effect on brand image with a p value of 0.000 <0.05. The brand image variable itself did not have a significant effect on the intention to return patients (p value 0.076> 0.05). Brand image was also unable to mediate the influence of the two eWOM-instagram variables and service quality on the intention to return patients where the p values ​​were 0.636 and 0.124, respectively. The absence of a relationship between eWOM-IG and brand image on the interest in patient return visits is due to the fact that there are still respondents who are not active users of Instagram social media so they are less updated with the hospital profile updated via Instagram. This study found that service quality has a significant effect on brand image and patient return visit interest because it can be used as input for the hospital. The hospital also needs to further consider the use of Instagram social media in conducting promotions that are easily accessible to the community in their area so that they can be right on target in their use, such as by including Instagram links or IDs in various hospital promotional media.